Hepatitis E in Canadian blood donors. Issue 6 (10th April 2017) - Fearon, Margaret A.; O'Brien, Sheila F.; Delage, Gilles; Scalia, Vito; Bernier, France; Bigham, Mark; Weger, Steven; Prabhu, Sneha; Andonov, Anton
Abstract : BACKGROUND: Hepatitis E virus (HEV) is a virus of emerging importance to transfusion medicine as studies on blood donors and other populations demonstrate that the prevalence of endemic cases is higher than previously recognized and the risk to vulnerable transfusion recipients is not insignificant. STUDY DESIGN AND METHODS: We carried out an HEV prevalence study on 13, 993 Canadian blood donors with polymerase chain reaction (PCR) testing on all donors and antibody testing on a subset of 4102 donors. HEV antibody–positive and age‐ and sex‐matched antibody‐negative donors were invited to participate in a scripted telephone interview about risk factors. RESULTS: There were no PCR‐positive samples found (95% confidence interval [CI], 0%‐0.026%). The seroprevalence of HEV in our tested population was 5.9% (95% CI, 5.16%‐6.59%). HEV antibody positivity was associated with male sex and increasing age. In case‐control analysis history of living outside Canada (odds ratio [OR], 2.9; 95% CI, 1.56‐5.32) and contact with farm animals (OR, 1.5; 95% CI, 1.01‐2.28) were associated with HEV seropositivity. CONCLUSION: This is the largest data set to date on HEV infection in Canada. Results suggest low lifetime exposure to HEV and that infectious donations are rare.